2015
DOI: 10.1371/journal.pone.0125122
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-Induced Vascular Progenitor Differentiation towards Endothelial Lineage via MiR-21/Akt/β-Catenin Is Protective in Vessel Graft Models

Abstract: Background and PurposeVessel graft failure is typically associated with arteriosclerosis, in which endothelial dysfunction/damage is a key event. Resveratrol has been shown to possess cardioprotective capacity and to reduce atherosclerosis. We aimed to study the influence of resveratrol on the behavior of resident stem cells that may contribute to graft arteriosclerosis.Experimental ApproachVascular resident progenitor cells and embryonic stem cells were treated with resveratrol under differentiating condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Bai et al (16) demonstrated that treatment with resveratrol restrained isoflurane-induced neuroapoptosis by activating the Akt signaling pathway. Campagnolo et al (26) reported that resveratrol reduced neointimal formation in a vascular graft model through microRNA-21/Akt/β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al (16) demonstrated that treatment with resveratrol restrained isoflurane-induced neuroapoptosis by activating the Akt signaling pathway. Campagnolo et al (26) reported that resveratrol reduced neointimal formation in a vascular graft model through microRNA-21/Akt/β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors showed that vascular progenitor cells treated ex vivo with RSV produced better endothelialization of the decellularized vessels. Moreover, they demonstrated that RSV-enriched diet reduces lesion formation in a mouse model of vessel graft [153].…”
Section: Stilbenesmentioning
confidence: 99%
“…This downregulation of miR-20b was proposed to be linked with the potent anti-angiogenic action of RSV in the ischemic myocardium and with the synergic effects of RSV and γ-tocotrienol. An elegant and complex study performed by Campagnolo et al showed that RSV can induce the expression of endothelial markers, such as CD31, VE-cadherin and eNOS in vascular resident progenitor cells and embryonic stem cells [153]. They also demonstrated that RSV significantly reduced miR-21 expression in these cells, which in turn diminished protein kinase B (PKB) phosphorylation.…”
Section: Stilbenesmentioning
confidence: 99%
“…Resveratrol‐regulated miRNAs also had effects on lipid metabolism in adipose tissues, mitochondrial function in skeletal muscles, and osteoporosis in ovariectomized rats . In addition, resveratrol‐regulated miRNAs played neuroprotective roles and had beneficial effects in preclinical models of Parkinson's and Alzheimer's disease and vessel graft . Finally, anti‐inflammatory effects of resveratrol‐regulated miRNAs have also been reported .…”
Section: Mirna‐mediated Epigenetic Actions Of Resveratrol and Analogsmentioning
confidence: 94%